Anti-apoptotic and Immunomodulatory Effect of CB2 Agonist, JWH133, in a Neonatal Rat Model of Hypoxic-Ischemic Encephalopathy - Gupta, Bhavna; Hornick, Mary G.; Briyal, Seema; Donovan, Ramona; Prazad, Preetha; Gulati, Anil (Frontiers in Pediatrics, 2020)
Introduction: Neonatal HIE is associated with high morbidity and mortality. Current research, is focused on developing alternative treatments to therapeutic hypothermia for treatment of HIE. The endocannabinoid system is known to be influential in neuronal protection. Activation of brain CB2 receptors, has been shown to reduce inflammatory markers and decrease infarct volume in adult cerebral ischemic models. Methods: Rat pups were divided into six groups: 1 – Placebo; 2 – JWH133; 3 – HIE + Placebo; 4 – HIE + JWH133; 5 – HIE + Hypothermia + Placebo; and 6 – HIE + Hypothermia + JWH133. HIE was induced in in groups 3-6 by right carotid ligation on postnatal day 7 followed by placement in a hypoxic chamber. Pups in groups 5 and 6 were treated with hypothermia. Western blot analysis was used to analyze brain tissue for acute inflammatory markers (IL-6, TNFα, MIP1α, and RANTES), immunoregulatory cytokines (TGFβ and IL-10), and CB2 receptor expression. DNA fragmentation in the brains of pups was determined via TUNEL staining post HIE. Results: The combination of JWH133 and hypothermia significantly reduced tumor necrosis factor α (TNFα) (-57.7%, P=0.0072) and macrophage inflammatory protein 1α (MIP1α) (-50.0%, P=0.0211) as compared to placebo. DNA fragmentation was also significantly reduced, with 6.9±1.4 % TUNEL+ cells in HIE+JWH133 and 12.9±2.2 % in HIE+Hypothermia+JWH133 versus 16.6±1.9 % in HIE alone. No significant difference was noted between groups for the expression of interleukins 6 and 10, RANTES, or TGFβ. After 8 hours, CB2 receptor expression increased nearly 2-fold in the HIE and HIE + JWH133 groups (+214%, P=0.0102 and +198%, P=0.0209, respectively) over placebo with no significant change in the hypothermia groups. By 24 hours post HIE, CB2 receptor expression was elevated over five times that of placebo in the HIE (P<0.0001) and HIE + JWH133 (P=0.0002) groups, whereas hypothermia treatment maintained expression similar to that of placebo animals. Conclusion: These results indicate that the combination of CB2 agonist and hypothermia may be neuroprotective in treating HIE, opening the door for further studies to examine alternative or adjuvant therapies to hypothermia.